Studi Desain High Temperature Gas-Cooled Reactor (HTGR) Berpendingin Gas Hidrogen Menggunakan Bahan Bakar Thorium - Dika Riyan Saputra; Yanti Yulianti; Agus Riyanto (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2019)
The Research of design reactor HTGR cell core with thorium fuel and hydrogen gas cooled using SRAC program has been done. The reactor was designed to generate maximum thermal power and critical conditions. The parameters on this study are fuel enrichment, atomic density, size and configuration of reactor core, criticality and the distribution of power density. Reactor core calculation was done in two dimensional core (x,y) at 1/6 part of the reactor core with a triangular mesh. The fuel was Th232 and U233, and hydrogen as coolant. In this study, the ideal reactor core design was length (x) was 428 cm and width (y) was 214 cm, the first fuel enrichment was 6,037% and second fuel enrichment was 8%. Reactor core design in this study generated 60 MWth thermal power with maximum power density was 179,6747 Watt/cm3 which is located at x=1, y=18 point and effective multiplication (keff) is 1,000005.